THE EFFECT OF TAX RATE PERCEPTION, TAX UNDERSTANDING, AND TAX SANCTIONS ON TAX COMPLIANCE WITH SMALL AND MEDIUM ENTERPRISES (MSME) IN SUKOHARJO - M. Hasan Ma'ruf; Sri Supatminingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine whether there is a partial influence on knowledge of taxation, tax regulations and tax benefits. The sampling technique in this study used simple rondom sampling, then obtained a study sample of 100 MSME tax payers. Data analysis techniques performed by descriptive statistical tests, classical assumptions, hypothesis testing with linear regression analysis. The results showed that knowledge of taxation and tax regulations had a positive effect on MSME taxpayer compliance in KPP Pratama Sukoharjo while the tax benefits did not affect MSME taxpayer compliance in KPP Pratama Sukoharjo. Keywords: Tax compliance, tax knowledge, tax benefits and tax compliance